Neonatal staphylococcal scalded skin syndrome: an outbreak in a Neonatal Intensive Care Unit in Portugal - Marta Ezequiel; Olga Voutsen; Manuel Cunha; Rosalina Barroso (Hygeia Press di Corridori Marinella, 2019)
Staphylococcal scalded skin syndrome (SSSS) is a blistering skin condition caused by exfoliative toxin-producing strains of S. aureus. It usually occurs in children under 5 years old but is rare in neonates, especially in very low birth weight, premature infants. Although infrequently, clinical outbreaks have been reported. We describe an outbreak of SSSS that occurred among 3 premature infants admitted to a level III Neonatal Intensive Care Unit (NICU). As soon as it was realized that there was an outbreak, the Infection Control Commission (ICC) was informed and measures to contain the outbreak were immediately applied.